2001
DOI: 10.1159/000050385
|View full text |Cite
|
Sign up to set email alerts
|

Membranous Obstruction of the Fourth Ventricle Outlet

Abstract: We report the case of a 15-year-old girl with amenorrhea and a several-week history of headache. After the diagnosis of membranous obstruction of the foramen of Magendie suggested by MRI, suboccipital craniotomy for removal of the membrane was carried out. The patient made an excellent postoperative recovery, and postoperative phase-contrast MRI demonstrated patent cerebrospinal fluid (CSF) pathways at the level of the foramina of Magendie and Luschka. We believe that this case is of interest because of the un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 5 publications
(3 reference statements)
1
23
0
Order By: Relevance
“…Although this assumption seems to be against traditional concept, a few case reports have been published with only 1 exit foramen of the fourth ventricle obstructed, causing tetraventricular hydrocephalus and responding to surgery. [23][24][25][26][27][28][29][30][31][32] These results overlap with observation in our large study cohort. The second step was the acquisition of the 3D-CISS sequence to determine whether there was obstructing membrane either within or outside the ventricular system.…”
Section: Mr Evaluationsupporting
confidence: 89%
“…Although this assumption seems to be against traditional concept, a few case reports have been published with only 1 exit foramen of the fourth ventricle obstructed, causing tetraventricular hydrocephalus and responding to surgery. [23][24][25][26][27][28][29][30][31][32] These results overlap with observation in our large study cohort. The second step was the acquisition of the 3D-CISS sequence to determine whether there was obstructing membrane either within or outside the ventricular system.…”
Section: Mr Evaluationsupporting
confidence: 89%
“…The cisterns retard and direct the flow of CSF [21]: ‘Thus the opening of one cistern does not allow the immediate egress of fluid from the adjoining cisterns and collapse of the entire subarachnoid space.’ [21]. There is no clear reason why such small openings cannot be obstructed and lead to a blockage of the CSF whereas all outlets of the 4th ventricle can be blocked [22, 23]. Especially bleedings or inflammations may lead to obstructions of the small cisternal opening; in one of the presented cases, the resection of the ependymoma with minor hemorrhage or inflammation might have been the reason of intracisternal block.…”
Section: Discussionmentioning
confidence: 99%
“…6) However, some authors reported that the cases who performed fourth ventriculostomy did not require the placement of a catheter to maintain its patency. 4,5,10) Posterior fossa craniotomy and membrane excision are still advocated by some. 10,11) Suboccipital craniectomy is an invasive procedure; suboccipital craniectomy with microsurgical exploration of the foramen of Magendie and excision of the obstructing membranes with or without a catheter to maintain the communication between the ventricular cavity and the subarachnoid space is a more physiological approach.…”
Section: 7)mentioning
confidence: 99%
“…4,5,10) Posterior fossa craniotomy and membrane excision are still advocated by some. 10,11) Suboccipital craniectomy is an invasive procedure; suboccipital craniectomy with microsurgical exploration of the foramen of Magendie and excision of the obstructing membranes with or without a catheter to maintain the communication between the ventricular cavity and the subarachnoid space is a more physiological approach. 7) Early in 1962, a new modality of fourth ventriculocisternostomy using a polyethylene catheter was described.…”
Section: 7)mentioning
confidence: 99%